2015
DOI: 10.1063/1.4913646
|View full text |Cite
|
Sign up to set email alerts
|

Application of an ice thermal energy storage system as ways of energy management in a multi-functional building

Abstract: Peak-hour tariff typically troubles commercial office buildings in hot and humid climates where cooling demands are high during summer. Because the local power company rate structure strongly favors the practice of load shift and conversely penalizes peak load demand during peak hours, a multi-functional office building in Taipei seeks to reduce its cooling cost by ways of an ice thermal energy storage system in which harvested ice is stored during cheaper off-peak hours and thawing the storage medium during p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…There are three kinds of TES systems as stated by [63]. (1) The sensible thermal storage system (STES) which is based on storing thermal energy by heating or cooling a liquid or solid medium (e.g., in our case, ice thermal storage system for cooling [64]). The compressed air energy storage system [65] and ATES (aquifer thermal energy system) for heat or cool thermal storage in aquifers) [66].…”
Section: Thermal Energy Storage Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are three kinds of TES systems as stated by [63]. (1) The sensible thermal storage system (STES) which is based on storing thermal energy by heating or cooling a liquid or solid medium (e.g., in our case, ice thermal storage system for cooling [64]). The compressed air energy storage system [65] and ATES (aquifer thermal energy system) for heat or cool thermal storage in aquifers) [66].…”
Section: Thermal Energy Storage Systemsmentioning
confidence: 99%
“…Ice thermal storage tank for cooling [64]: This is a system that can be used combined with other parts in plants for cooling (see Figure 1 in [64]). Built-in ice storage is ideal for IST (ice storage tank).…”
Section: Thermal Energy Storage Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the Demand Response Quick Assessment Tool (DRQAT) model, they concluded that ice storage could reduce the buildings' electricity consumption by about 1500 kWh at peak times [29]. Moreover, Wu et al, modelled ice storage in a building and concluded that using this technology reduces costs by 37% per year and reduces peak energy consumption by 800 kWh [30]. Lee et al studied the effect of the ice storage system by using a building simulation model and concluded that peak energy consumption is reduced by 30% [31].…”
Section: Introductionmentioning
confidence: 99%